INCOME ANALYSIS OF ZEA MAYS L. FARMING BUSINESS IN RUMPIN DISTRICT, BOGOR REGENCY - Rahmadona, Lola; Azlansyah, Muhammad (Journal of Agri Socio Economics and Business, 2024)
Zea mays L. is one of the productive commodities cultivated in Rumpin District, Bogor Regency. Although Rumpin Regency has potential, it is faced with several problems, namely the high price of fertilizers, the widespread use of similar pesticides, high labor costs, the high price of diesel fuel for the operational needs of agricultural machinery and equipment, and differences in the use of tools and machinery by each farmer in Zea mays L. cultivation activities. The purpose of this research is to analyze the production costs, income, and income efficiency of Zea mays L. farming in Rumpin District. The method used in this research is quantitative. Production cost expenditures were analyzed using cost analysis methods, and farming income efficiency was determined using R/C ratio analysis. The results showed that the total cost incurred was IDR 17,587,098/ha with a cash cost of IDR 7,486,439/ha and non-calculated costs of IDR 10,100,659/ha. Zea mays L. farming resulted in a positive average total income value. Income from cash costs was IDR 21.266.894/ha, and income from total costs was IDR 11.166.235/ha. The R/C ratio for cash costs was 5.17, and the R/C ratio for total costs was 2.42. This profitable Zea mays L.farming business can be continued by farmers in Rumpin District, Bogor Regency.